COVID-19: Are Malaysians embracing or suffering the new normality? - Dinyadarshini Johnson; Stanley Eng Chee Ren; Hema Darshinee Johnson; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
The COVID-19 pandemic has inevitably rendered a paradigm shift in peoples’ day-to-day normality. The pandemic has precipitated various reaction and responses from people across the globe especially with the enforcement of preventive measures initiated by their respective government forces. The movement control order (MCO) was one of the drastic measures taken in Malaysia adhering to the guideline released by World Health Organization (WHO) and has been made effective since 18th of March 2020. The execution of MCO in a developing setting like Malaysia certainly impacts its people on several fronts, especially those from low-socioeconomic background. It creates a domino effect from an economical to psychological aspects at both societal and individual levels. Subsequently, a conditional MCO (CMCO) has been introduced during midway through Phase 4 of MCO with eased restrictions, particularly considering economic downturn. CMCO is followed by recovery MCO (RMCO) phase. In this article, we aim to share some insights while highlighting the impacts of COVID-19 with an emphasize on the psychosocial aspect, particularly during MCO phases, which has thus imposed a new normality on Malaysians.